If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(9 + 2x) = -90 (9 * -6 + 2x * -6) = -90 (-54 + -12x) = -90 Solving -54 + -12x = -90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '54' to each side of the equation. -54 + 54 + -12x = -90 + 54 Combine like terms: -54 + 54 = 0 0 + -12x = -90 + 54 -12x = -90 + 54 Combine like terms: -90 + 54 = -36 -12x = -36 Divide each side by '-12'. x = 3 Simplifying x = 3
| 26-3.50x=8.50 | | 8=m+24 | | X+5x-5=13-3x | | 8x^2=5x+3 | | 2u^2-11u+5=0 | | 4(2-2x)=-80 | | 2x+36=4x+20 | | -4+.8x=-6 | | .5x-1=-1 | | 3(5x-10)=-75 | | -5(6x-1)=-265 | | 5x-9y=-3 | | 7(2x+6)=-98 | | 5(n+3)m+5=-25 | | 6(7x+4)=192 | | 6w+8=3w-5 | | 4x+12=9x-13 | | -7(-6x+6)=-126 | | 3(4-x)-6(4-3)=3 | | 6(-6+7x)=174 | | 2x+6y=230 | | -5(4x+4)=-120 | | -56=-21y | | 2(2+x)=22 | | 3r+7=3 | | 2w^2=-5w-3 | | -4n+7+6n=19 | | 45x+81=0 | | -f=gt-i | | 5(-8+7x)=65 | | 5(2x+40)=30 | | 5(2x+7)=135 |